Narrative Strategies and Intermedial Devices in Gabriel Josipovici’s In the fertile Land - Mário Semião (Revue LISA)
Even though his novelistic work by far exceeds his output in short fiction, Gabriel Josipovici’s contribution to this genre is nothing less than significant. This investigation focuses on the third of his collections of short stories, In the Fertile Land (1987). The motifs and narrative techniques in Josipovici’s work are wide-ranging and display a great variety of thematic concerns. Yet, this collection of short stories seems to demonstrate a particular emphasis on two recurrent features in Josipovici’s oeuvre: the presence of a metafictional dimension and an intermedial aspect in his writing. In proposing this double emphasis, the notions of metafiction and intermediality are initially discussed in the context of a close reading of one of the stories in the collection, “Brothers” (1983). The study of this four-page story focuses on how the structure of the text not only incorporates a violation of narrative levels which acts as a metafictional strategy, but also on how that same disruption is linked with Karlheinz Stockhausen’s musical techniques. In “Brothers” one finds these two features of Josipovici’s writing working simultaneously as a means of foregrounding the text’s own linguistic and textual premises. Following the survey of “Brothers” as a self-reflexive text, this study aims to argue for the particular relevance of In the Fertile Land in Josipovici’s oeuvre because of its varied and systematic use of these two characteristic features in his writing, which in turn call attention to the narrative process itself, a concern that pervades both the author’s fictional and non-fictional work.